Desenvolvimento de um modelo lagrangiano para estimar a dispersão de escalares passivos em condições de meandro do vento horizontal - Stefanello, Michel Baptistella (2017)
The description of the effects of the wind meandering in the scalar dispersion is a challenging task, since this type of flow represents a physical state characterized by multiple scales. In this study, a Lagrangian stochastic diffusion model is derived to describe the scalar transport during the horizontal wind meandering phenomenon, occurring in a PBL. The model is derived from the linearization of the Langevin equation and employs a heuristic functional form, which represents the autocorrelation functions of the meandering. The new solutions, which describe the longitudinal and lateral wind components, were used to simulate two experiments of contaminants dispersion in low-wind conditions, INEL (USA) and GRAZ (Austria). The results of the comparison indicate that the new model reproduces fairly well the observed concentrations of contaminants and, therefore, satisfactorily describes the enhanced dispersion due to the presence of meandering.